2022
DOI: 10.3389/fcimb.2022.1004148
|View full text |Cite|
|
Sign up to set email alerts
|

Heme oxygenase-1 modulates ferroptosis by fine-tuning levels of intracellular iron and reactive oxygen species of macrophages in response to Bacillus Calmette-Guerin infection

Abstract: Macrophages are the host cells and the frontline defense against Mycobacterium tuberculosis (Mtb) infection, and the form of death of infected macrophages plays a pivotal role in the outcome of Mtb infections. Ferroptosis, a programmed necrotic cell death induced by overwhelming lipid peroxidation, was confirmed as one of the mechanisms of Mtb spread following infection and the pathogenesis of tuberculosis (TB). However, the mechanism underlying the macrophage ferroptosis induced by Mtb infection has not yet b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…Likewise, the induction of these molecules was more pronounced in the PA57 group compared to MSSA60. Furthermore, we identified the molecular fingerprint suggesting increased ferroptosis in stimulated cells with induction of heme oxygenase 1 (HO-1) as a key marker and regulator of the process [ 35 ]. Similarly to other PCD programs, ferroptosis seems to be more induced in PA57-stimulated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the induction of these molecules was more pronounced in the PA57 group compared to MSSA60. Furthermore, we identified the molecular fingerprint suggesting increased ferroptosis in stimulated cells with induction of heme oxygenase 1 (HO-1) as a key marker and regulator of the process [ 35 ]. Similarly to other PCD programs, ferroptosis seems to be more induced in PA57-stimulated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…During Mtb infection, the accumulation of ROS and lipid peroxides can promote tissue damage and the spread of pathogenic bacteria. However, HO‐1 can increase the content of ferrous metals, thereby promoting the survival of Mtb 134,135 …”
Section: Ferroptosismentioning
confidence: 99%
“…Meanwhile, ferroptosis-related gene suppressor of cytokine signaling 1 (SOCS1) is a biomarker for the diagnosis and treatment of MTB [96] (Table 2). A recent study found that heme oxygenase-1 (HMOX1) is an important regulator of MTB-induced ferroptosis, regulating ROS production and iron accretion, thus changing the outcome of macrophage death after MTB infection [97]. It is suggested that excess iron significantly reduces resistance to mycobacterial infection now that macrophages lose their ability to kill intracellular pathogens in a NO-mediated mechanism during iron overload [98][99][100].…”
Section: Bacterial Infectionmentioning
confidence: 99%